On the Applications of EMG Sensors and Signals - Kamavuako, Ernest N. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint captures the latest advances in Electromyography (EMG) sensor development, EMG sensor applications, and EMG signal conditioning using theoretical and experimental approaches. This report is timely, as EMG sensors and signals have applications in many domains. This reprint provides a snapshot of several exciting EMG sensor and signal applications: swallowing, motion detection and prostheses control, muscle synergies, robotic exoskeleton, driver's behaviour, signal conditioning, and muscle assessment.